"Tasting" the cerebrospinal fluid: Another function of the choroid plexus?. (21st April 2016) - Tomás, J.; Santos, C.R.A.; Quintela, T.; Gonçalves, I.
Highlights: Proteins encoding the taste transduction machinery are present in rat choroid plexus. Rat choroid plexus epithelial cells respond to the bitter compoundd -Salicin. Probenecid inhibits choroid plexus epithelial cells response tod -Salicin. The bitter transduction signalling pathway is functional in the choroid plexus. Abstract: The choroid plexus (CP) located in brain ventricles, by forming the interface between the blood and the cerebrospinal fluid (CSF) is in a privileged position to monitor the composition of these body fluids. Yet, the mechanisms involved in this surveillance system remain to be identified. The taste transduction pathway senses some types of molecules, thereby evaluating the chemical content of fluids, not only in the oral cavity but also in other tissues throughout the body, such as some cell types of the airways, the gastrointestinal tract, testis and skin. Therefore, we hypothesized that the taste transduction pathway could also be operating in the CP to assess the composition of the CSF. We found transcripts for some taste receptors ( Tas1r1, Tas1r2, Tas1r3, Tas2r109 and Tas2r144 ) and for downstream signaling molecules ( α-Gustducin, Plcβ2, ItpR3 and TrpM5 ) that encode this pathway, and confirmed the expression of the corresponding proteins in Wistar rat CP explants and in the CP epithelial cells (CPEC). The functionality of the T2R receptor expressed in CP cells was assessed by calcium imaging, of CPEC stimulated with the bitter compoundd -Salicin, which elicited a rise in the intracellular Ca 2+ . This effect was diminished in the presence of the bitter receptor blocker Probenecid. In summary, we described the expression of the taste-related components involved in the transduction signaling cascade in CP. Taken together, our results suggest that the taste transduction pathway in CPEC makes use of T2R receptors in the chemical surveillance of the CSF composition, in particular to sense bitter noxious compounds.